Lean companies in the track of sustainability - Abreu, Florentina (2015)
This paper will present a literature review on companies’ practices of sustainability and this relationship with the Lean concept, if there is any. When this relationship is established, normally, it is coined as Lean-Green. In today´s highly competitive markets, with accelerating global development, the increasing resource use and environmental impacts, the business as usual is not a choice for a sustainable future. A true Lean company is a sustainable company by the Lean culture embed, that is “doing more with less”.